2011
DOI: 10.1242/dev.056929
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Dlx5 and Dlx6 expression by Hand2 is essential for initiation of tongue morphogenesis

Abstract: SUMMARYLower jaw development is a complex process in which multiple signaling cascades establish a proximal-distal organization. These cascades are regulated both spatially and temporally and are constantly refined through both induction of normal signals and inhibition of inappropriate signals. The connective tissue of the tongue arises from cranial neural crest cell-derived ectomesenchyme within the mandibular portion of the first pharyngeal arch and is likely to be impacted by this signaling. Although the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(107 citation statements)
references
References 74 publications
5
101
0
1
Order By: Relevance
“…The tongue of most frogs can be flipped out quickly to catch insects and other prey, and their tongue is morphologically specialized to accomplish this function. HAND2 plays important roles in tongue morphogenesis by regulating expression levels of other genes, including Dlx5 and Dlx6 (22). PRDM16 is also necessary for normal palatogenesis (23).…”
Section: Resultsmentioning
confidence: 99%
“…The tongue of most frogs can be flipped out quickly to catch insects and other prey, and their tongue is morphologically specialized to accomplish this function. HAND2 plays important roles in tongue morphogenesis by regulating expression levels of other genes, including Dlx5 and Dlx6 (22). PRDM16 is also necessary for normal palatogenesis (23).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we reported that Hand2 affects cell proliferation (Hendershot et al, 2008;Holler et al, 2010;Barron et al, 2011). The significant decrease observed in both neuron and glial cell numbers in Hand2 mutant ENS suggested that loss of Hand2 function in the NEP cells might cause this anomaly.…”
Section: Hand2 Affects Proliferation Of Neural Precursor Cellsmentioning
confidence: 89%
“…We have previously shown that Hand2 functions in neurogenesis (Hendershot et al, 2008), development of the cardiac outflow tract (Holler et al, 2010) and aspects of craniofacial morphogenesis (Barron et al, 2011) by regulating cell proliferation. Here, we show a significant decrease in the number of dividing NEP cells when Hand2 was deleted although there was only a slight decrease in the total number of neurons.…”
Section: Targeted Deletion Of Hand2 Alters Encc Proliferationmentioning
confidence: 99%
“…Targeted disruption of Twist1 in NCCs leads to defects in upper and lower jaw development (Bildsoe et al, 2009). NCC-specific deletion of Hand2 results in disruption of lower jaw and tongue development (Barron et al, 2011). These factors appear highly conserved during vertebrate evolution (Barnes and Firulli, 2009) and probably play similar roles in human facial development.…”
Section: Introductionmentioning
confidence: 99%